The diabetes cardiovascular outcomes trials and racial and ethnic minority enrollment: impact, barriers, and potential solutions - Sinclair, Matthew R.; Ardehali, Mariam; Diamantidis, Clarissa J.; Corsino, Leonor (Frontiers in Public Health, 2024)
Type 2 diabetes (T2D) affects millions of individuals worldwide and is a well-documented risk factor for cardiovascular (CV) disease and chronic kidney disease, both of which are leading causes of mortality. Racial and ethnic minority groups in the US, including but not limited to Hispanic/Latino, non-Hispanic Black, and Southeast Asian individuals, are disproportionately burdened by both T2D and its adverse outcomes. In recent years, there have been numerous cardiovascular outcomes trials (CVOTs) on novel antidiabetic therapies, including the dipeptidyl peptidase-4 inhibitors, glucagon-like peptide-1 (GLP-1) receptor agonists (RAs), and sodium-glucose cotransporter-2 (SGLT2) inhibitors. CVOTs’s initial aim was to demonstrate the cardiovascular safety of these drugs. Unexpected CV and kidney protective effects were found, specifically among the GLP-1 RAs and the SGLT2 inhibitors. These benefits informed the new paradigm of the management of patients with T2D. However, some experts argued that the lack of racial and ethnic minority group representation in these trials represented a challenge. While the downstream effects of this lack of representation must be further elucidated, it is clear and recognized that efforts need to be made to include a more representative sample in future CVOTs, specifically including individuals from those groups most burdened by T2D and its complications, if clinicians are to have an accurate picture of the benefits and potential pitfalls of utilizing these drugs in a real-world setting. In this comprehensive review, we briefly summarize the significant findings from the CVOTs, report the lack of representation of Hispanic/Latino, non-Hispanic Black, and Southeast Asian individuals in the CVOTs, investigate the barriers to recruiting racial and ethnic minority groups into clinical trials, and suggest potential solutions to overcome these obstacles at the patient-, provider-, and sponsor/system-level in future trials.